A new looped-functional for stability analysis of sampled-data systems - Zeng, H.; Teo, Kok Lay; He, Y. (Pergamon Press, 2016)
In this paper, a new two-sided looped-functional is introduced for stability analysis of sampled-data systems. The functional fully utilizes the information on both the intervals x(t) to x(tk) and x(t) to x(tk+1). Based on the two-sided functional, an improved stability condition is derived in the form of linear matrix inequality (LMI). Numerical examples show that the result computed by the presented condition approximates nearly the theoretical bound (bound obtained by eigenvalue analysis) and outperforms substantially others in the existing literature.